Comparison of radiation exposure associated with intraoperative cone-beam computed tomography and follow-up multidetector computed tomography Angiography for evaluating endovascular aneurysm repairs - Steuwe, Andrea; Geisbüsch, Philipp; Schulz, Christof; Böckler, Dittmar; Kauczor, Hans-Ulrich; Stiller, Wolfram (Journal of endovascular therapy, 2016)
Purpose: To compare the radiation exposure associated with intraoperative contrast-enhanced cone-beam computed tomography (ceCBCT) acquisitions to standard 3-phase multidetector computed tomography (MDCT) angiography used for assessing technical success after endovascular aortic repair (EVAR). Methods: Effective doses (EDs) were calculated for 66 EVAR patients (mean age 71 years; 61 men) with a mean 27.7-kg/m2 body mass index (range 17-49) who had both intraoperative ceCBCT and postoperative 3-phase MDCT angiography between November 2012 and April 2015. In addition, EDs were directly determined using thermoluminescent dosimeters (TLDs) embedded in anthropomorphic phantoms with body mass indexes of 22 and 30 kg/m2. Effective doses were calculated by summing doses recorded by all TLDs corresponding to a specific tissue type before applying the International Commission on Radiological Protection (ICRP) 60 and 103 weighting factors. EDs were compared with each other for both imaging modalities as well as to TLD measurements. Results: Average EDs of the patient collective were 4.9±1.1 mSv for ceCBCT, 2.6±1.2 mSv for single-phase MDCT (46% decrease, covering solely the area of the implanted endograft), and 13.6±5.5 mSv for comprehensive 3-phase MDCT examinations (178% increase, anatomical coverage from the aortic arch to femoral artery bifurcation). EDs determined in phantom measurements ranged from 3.1 to 4.5 mSv for ceCBCT, amounting to 2.6 mSv for a single MDCT phase (15% to 40% decrease) using ICRP 60 conversion factors. Applying ICRP 103 factors resulted in higher values for ceCBCT and slightly lower ones for MDCT. Conclusion: ceCBCT offers the chance for immediate intraoperative revisions of endograft-related problems. Requiring only a single-phase acquisition, ceCBCT is associated with a considerable reduction in ED (50%-75%) compared to standard 3-phase MDCT angiography after EVAR. On the other hand, MDCT has a larger field of view and is associated with less radiation exposure for a single phase (reduction of 20%-60%) if only the stented region is covered; however, MDCT angiography also uses larger amounts of contrast.